In Operando Angle‐Resolved Photoemission Spectroscopy with Nanoscale Spatial Resolution: Spatial Mapping of the Electronic Structure of Twisted Bilayer Graphene. Issue 6 (30th March 2021) - Majchrzak, Paulina; Muzzio, Ryan; Jones, Alfred J. H.; Curcio, Davide; Volckaert, Klara; Biswas, Deepnarayan; Gobbo, Jacob; Singh, Simranjeet; Robinson, Jeremy T.; Watanabe, Kenji; Taniguchi, Takashi; Kim, Timur K.; et al.
Abstract : To pinpoint the electronic and structural mechanisms that affect intrinsic and extrinsic performance limits of 2D material devices, it is of critical importance to resolve the electronic properties on the mesoscopic length scale of such devices under operating conditions. Herein, angle‐resolved photoemission spectroscopy with nanoscale spatial resolution (nanoARPES) is used to map the quasiparticle electronic structure of a twisted bilayer graphene device. The dispersion and linewidth of the Dirac cones associated with top and bottom graphene layers are determined as a function of spatial position on the device under both static and operating conditions. The analysis reveals that microscopic rotational domains in the two graphene layers establish a range of twist angles from 9.8° to 12.7°. Application of current and electrostatic gating lead to strong electric fields with peak strengths of 0.75 V/μm at the rotational domain boundaries in the device. These proof‐of‐principle results demonstrate the potential of nanoARPES to link mesoscale structural variations with electronic states in operating device conditions and to disentangle such extrinsic factors from the intrinsic quasiparticle dispersion. Abstract : Nanoscale angle‐resolved photoemission spectroscopy is applied to map the electronic structure of a twisted bilayer graphene device during the application of current and an electrostatic gate voltage. Rotational domains are found to strongly affect the measured linewidth of the top and bottom Dirac cones and lead to a spatially inhomogeneous electric field during operation of the device.